Immediate Loading of Single Implants in the Anterior Maxilla: A 1-Year Prospective Clinical Study on 34 Patients - Miguel Stanley; Filipa Calheiros Braga; Beatriz Mota Jordao (Hindawi Limited, 2017)
Purpose. To present the outcomes of immediately loaded single implants placed in the anterior maxilla. Methods. Over a 2-year period, all patients referred to a private clinic were considered for enrolment in this study. Inclusion criteria were single-tooth placement in postextraction sockets or healed sites of the anterior maxilla. All implants were immediately loaded and followed for a period of 1 year after the placement of definitive crowns. The outcome measures were implant stability, survival, and success. Results. 34 patients were selected and 43 tapered implants with a knife-edge thread design and a nanostructured, calcium-incorporated surface (Anyridge®, Megagen, Gyeongsang, Korea) were installed. Two implants were not sufficiently stable at placement (ISQ < 60) and were considered failed for immediate loading; 41 implants had an ISQ ≥ 60 at placement and were immediately loaded. One year after the placement of definitive crowns, no implant failures were reported, for a survival rate of 100%. No biological complications were found, but 2 implants had their prosthetic abutments loosened: the implant success rate was 95.2%. Conclusions. In the present study on the immediate loading of single implants in the anterior maxilla, positive outcomes were reported, with high survival (100%) and success (95.2%) rates (the present study has been registered in the ISRCTN registry, a publicly available trial register recognized by WHO and ICMJE, with number ISRCTN12935478).